Impacts of co‐occurring environmental changes on Alaskan stream fishes. (30th June 2020) - Murdoch, Alyssa; Mantyka‐Pringle, Chrystal; Sharma, Sapna
Abstract: Freshwater fishes are now facing unprecedented environmental changes across their northern ranges, especially due to rapid warming occurring at higher latitudes. However, empirical research that examines co‐occurring environmental effects on northern fish communities remains limited. We used fish community data from 1587 Alaskan stream sites to examine the potential combined and interacting effects of climate change, current weather, habitat, land use, and fire on two community‐level metrics (species richness, relative abundance), and on the distributions of three Alaskan fish species. Our models were 71–76% accurate in predicting the distribution of Alaskan stream fishes using a combination of climate and habitat variables. In contrast to other freshwater ecosystems that are most threatened by land use pressures, we did not detect any evidence for the potential stress of anthropogenic land use or fire on stream fishes. Warming temperatures increased overall community richness and abundance but produced differing responses at the species level. Juvenile salmon presence was positively associated with several climate variables including warmer spring and autumn temperatures and wetter summers. In comparison, warmer seasonal temperatures contributed to declines for northern‐adapted species such as Arctic grayling and Dolly Varden. This study highlights the overarching role of current and changing climate in regulating northern stream fish biodiversity. Although many fish species may benefit from climate change across their northern ranges, localised declines are likely to occur and may prove detrimental for communities with limited fishing portfolios. Climate change adaptation and mitigation strategies customised for rapidly changing northern ecosystems will play an essential role in preserving ecologically unique northern species.